Regulatory T cells: masterminds of immune equilibrium and future therapeutic innovations - Ge, Junwei; Yin, Xuan; Chen, Lujun (Frontiers in Immunology, 2024)
Regulatory T cells (Tregs), a subset of CD4+T cells marked by the expression of the transcription factor forkhead box protein 3 (Foxp3), are pivotal in maintaining immune equilibrium and preventing autoimmunity. In our review, we addressed the functional distinctions between Foxp3+Tregs and other T cells, highlighting their roles in autoimmune diseases and cancer. We uncovered the dual nature of Tregs: they prevented autoimmune diseases by maintaining self-tolerance while contributing to tumor evasion by suppressing anti-tumor immunity. This study underscored the potential for targeted therapeutic strategies, such as enhancing Treg activity to restore balance in autoimmune diseases or depleting Foxp3+Tregs to augment anti-tumor immune responses in cancer. These insights laid the groundwork for future research and clinical applications, emphasizing the critical role of Foxp3+Tregs in immune regulation and the advancement of next-generation immunotherapies.